Survey on Customer Satisfaction Towards Courier Services in Johor - Loo, Kelly; Mohd Asrah, Norhaidah (Enhanced Knowledge in Sciences and Technology, 2022)
The rapid rising of the e-commerce industry has boosted the courier industry in Malaysia. The courier service plays a vital role in delivering the products within the shortest time with the best condition. Courier companies should offer superb service quality to meet customer satisfaction and become the best choice in this competitive industry. This study aims to identify the customer preference on the courier service companies in Johor by using the descriptive analysis and the Chi-squared test. Next, to understand the factors that influence customer satisfaction toward the courier services using the gap analysis and SERVQUAL model. Lastly, to determine the relationship between cost, operation and satisfaction toward the courier services using the Spearman’s rank correlation coefficient. A total of 384 responses has been collected via Google form. The Cronbach’s alpha test revealed that the strength of relations is excellent for the five dimensions in the SERVQUAL model, namely reliability, assurance, tangibles, empathy, and responsiveness. The J&T Express is chosen as the most preferred courier company in Johor. The gap analysis showed that all five dimensions failed to meet the customer expectations. There are positive relationships between delivery cost and operation with customer satisfaction. The overall customer satisfaction score (CSAT) is 82.7% showed that the courier service must be enhanced. The courier company should improve the timeliness, customer service, facilities, parcel handling and employ good management strategies.